1957
DOI: 10.1107/s0365110x57002418
|View full text |Cite
|
Sign up to set email alerts
|

Structure cristalline de la forme triclinique duparadichlorobenzène

Abstract: Fo--Fc)] being obtained rapidly with the help of von Eller's photosommateTtr. An isotropic temperature factor was applied to the atoms C~. and C a but that for the atoms C1 and C 1 is strongly anisotropie.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…on DCB and to provide a basis for further spectroscopic and theoretical work in this laboratory. Under normal conditions, DCB crystallizes from the melt at 55°C in the triclinic (PT) ~-phase with Z= 1 (Housty & Clastre, 1957) and transforms to the common monoclinic a-phase (P21/a, Z = 2) at 30.8 °C (Frasson, Garbuglio & Bezzi, 1959). Below 0°C or at high pressure (Reynolds, Kjems & White, 1972;Balashov & Ikhemov, 1968) DCB crystallizes in a second monoclinic Z=2 modification, the ?-phase reported here.…”
Section: Introductionmentioning
confidence: 99%
“…on DCB and to provide a basis for further spectroscopic and theoretical work in this laboratory. Under normal conditions, DCB crystallizes from the melt at 55°C in the triclinic (PT) ~-phase with Z= 1 (Housty & Clastre, 1957) and transforms to the common monoclinic a-phase (P21/a, Z = 2) at 30.8 °C (Frasson, Garbuglio & Bezzi, 1959). Below 0°C or at high pressure (Reynolds, Kjems & White, 1972;Balashov & Ikhemov, 1968) DCB crystallizes in a second monoclinic Z=2 modification, the ?-phase reported here.…”
Section: Introductionmentioning
confidence: 99%
“…The structure is similar to that of the/3 form of pdichlorobenzene (Housty & Clastre, 1957), except that end-to-end C1... Cl contacts within the layers are replaced by side-to-side antiparallel nitrile-., nitrile contacts. It is apparently these antiparallel contacts that lead to the greater intermolecular attraction in the dinitrile (nitrile m.p.…”
mentioning
confidence: 66%
“…In all phases the molecules are located at inversion centres and in a-and y-DCB the orientations of the two molecules in the unit cell are related by reflection with respect to the ac plane. The positions and orientations of the molecules in the a-and /3-phase were determined in the late 1950s [6][7][8] and the d c b molecules seemed to be heavily distorted in the crystal. More accurate and detailed xray studies of the three phases at different temperatures later became available [10,11] and these new results showed that actually the d c b molecule in the crystal is almost regular and planar.…”
Section: Crystal Structure and Phononsmentioning
confidence: 99%
“…Moreover, the internal modes of the free t c b molecule were calculated for molecules with different 35C1/37C1 isotopic mass distributions and the isotope shifts were compared with the calculated 0953 In this contribution, we present similar calculations of the dispersion of the coupled internal vibrations in the a -, ¡3-and y-phase of 1,4-dichlorobenzene ( d c b ) . This crystal was chosen because it also exhibits a one-dimensional stacked crystal structure [6][7][8][9][10][11] and because investigations on the triplet electronic excitation by von Borczyskowski and co-workers [12,13] show that the interaction between equivalent molecules in the stacks (7||) is about two orders of magnitude larger than the interaction between inequivalent molecules. Calculations of the lattice modes (phonons) of a-and /3 -d cb have been reported earlier, and in particular the frequencies at k = 0 and the dispersion of the phonons have been investigated [2][3][4]14,15].…”
Section: Introductionmentioning
confidence: 99%